Which Notion of "Myth" in Emilio Garroni's Thought? Hypotesis and perspectives - Valentini, Antonio (Aesthetica Preprint, 2022)
The essay revolves around the attempt of outlining a possible physiognomy of the notion of “myth” in the light of the different treatment profiles that are offered in some places or passages – sometimes (comparatively) of short extension, but nevertheless of extreme theoretical relevance – of the philosophical reflection by Emilio Garroni. In particular, the essay highlights how the Garronian discourse authorizes a reading of the idea of “myth” which is fundamentally articulated at two levels, schematically translatable in the formulation of the following questions: 1) “under what conditions, first of all, we do experience of the world?” and 2) “in what way, starting from our being-in-the-world, is the project of its possible understanding and narration articulated and structured?”. If, in the first case, the notion of “myth” tends to be at one with the very idea of that “sense-feeling” (or that “sense to feel”) which constitutes the unobjectionable background of all our practices of knowing and/or of life, in the second case what it expresses is rather the way in which such a background pre-condition can be concretely exhibited in the sensitive determinacy of a representation.